Architecturosophy: Adventures of Architectural Concepts in the Twentieth Century - Lidin, Konstantin (project baikal, 2019)
The article considers emergence and development of several most influential philosophical ideas of the 20th century, which were applied to the architectural theory and practice. It presents a drastic change in architectural thinking of the 1930-1960s.
Keywords: architecture; history; theory; philosophy; XX century; paradigm shift